Macrofossil evidence of early sporophyte stages of a new genus of water fern Tecaropteris (Ceratopteridoideae: Pteridaceae) from the Paleogene Redbank Plains Formation, southeast Queensland, Australia. Issue 1 (2nd January 2016) - Rozefelds, Andrew C.; Dettmann, Mary E.; Clifford, H. Trevor; Lewis, Debra
Abstract : Rozefelds, A.C., Dettmann, M.E., Clifford, H.T. & Lewis, D., August 2015. Macrofossil evidence of early sporophyte stages of a new genus of water fern Tecaropteris (Ceratopteridoideae: Pteridaceae) from the Paleogene Redbank Plains Formation, southeast Queensland, Australia. Alcheringa 39, . ISSN 0311-5518. Water fern foliage is described from the Paleogene Redbank Plains Formation at Dinmore in southeast Queensland. The material, which is based upon leaf impressions, records early sporophyte growth stages. The specimens occur at discrete levels in clay pits at Dinmore, and the different leaf stages present suggest that they represent colonies of young submerged plants, mats of floating leaves, or a mixed assemblage of both. The leaf material closely matches the range of variation evident in young sporophytes of Ceratopteris Brongn., but in the complete absence of Cenozoic fossils of the spore genus Magnastriatites Germeraad, Hopping & Muller emend. Dettmann & Clifford from mainland Australia, which are the fossil spores of this genus, it is referred to a new genus, Tecaropteris . The record of ceratopterid-like ferns adds significantly to our limited knowledge of Cenozoic freshwater plants from Australia. The geoheritage significance of sites, such as Dinmore, is discussed briefly. Andrew C. Rozefelds [ andrew.rozefelds@qm.qld.gov.au ], Queensland Museum GPO Box 3300, South Brisbane, 4101, Queensland, Australia and School of Earth Sciences, University of Queensland, St Lucia, 4072, Queensland, Australia; Mary Dettmann [ mary.dettmann@qm.qld.gov.au ], H. Trevor Clifford [ trevor.clifford@qm.qld.gov.au ] and Debra Lewis [ debra.lewis@qm.qld.gov.au ], Queensland Museum, GPO Box 3300, South Brisbane, 4101, Queensland, Australia.